Atorvastatin attenuates ferroptosis-dependent myocardial injury and inflammation following coronary microembolization via the Hif1a/Ptgs2 pathway - Liu, Tao; Shu, Jin; Liu, Yangchun; Xie, Jian; Li, Tao; Li, Haoliang; Li, Lang (Frontiers in Pharmacology, 2022)
Objectives: Coronary microembolization (CME) represents a serious periprocedural complication after percutaneous coronary intervention. Ferroptosis has been identified in multiple cardiovascular diseases. In this study, we aimed to investigate the effects of atorvastatin (ATV) on ferroptosis and inflammation following CME and elucidate the underlying mechanism. Methods: We established a rat model of CME by injecting microspheres into the left ventricle. Deferoxamine (DFO), a selective ferroptosis inhibitor, or ATV was pretreated before modeling. Cardiac function and cardiac troponin T (cTnT) levels were detected. Levels of ferroptosis-associated genes, malondialdehyde (MDA), glutathione (GSH), and ferrous iron (Fe2+) were measured to validate ferroptosis. Levels of tumor necrosis factor alpha (TNF-α) and interleukin 1 beta (IL-1β) were assayed to determine the inflammation. Chromatin immunoprecipitation was performed to determine the binding of hypoxia-inducible factor 1 subunit alpha (Hif1a) to the promoter of prostaglandin-endoperoxide synthase-2 (Ptgs2). Results: Ferroptosis and inflammation were induced following CME with increased levels of MDA (~2.5 fold, p < 0.01), Fe2+ (~1.5 fold, p < 0.01), TNF-α, and IL-1β and decreased GSH levels (~42%, p < 0.01). Meanwhile, the level of Ptgs2 was significantly increased, while those of glutathione peroxidase 4 (Gpx4) and solute carrier family 7 member 11 (Slc7a11) were decreased. The level of cTnT was increased by 7-fold (p < 0.01). Left ventricular ejection fraction (LVEF) was significantly reduced (~85% in the sham group versus ~45% in the CME group, p < 0.01). DFO or Ptgs2 silencing inhibited the increase of MDA, Ptgs2, TNF-α, and IL-1β, and induced the levels of GSH and Gpx4, followed by reduction in cTnT levels by approximately 50% (p < 0.01). LVEF was improved by approximately 2 fold (p < 0.01). Mechanistically, the transcription factor Hif1a bound to the promoter of Ptgs2 and upregulated its expression. In addition, ATV inhibited the activation of the Hif1a/Ptgs2 axis and attenuated cardiac ferroptosis and inflammation, thus ameliorating CME-induced myocardial injury (LVEF, ~34% elevation; cTnT, ~1.8 fold decrease, p < 0.01). Conclusions: Atorvastatin ameliorates ferroptosis-mediated myocardial injury and inflammation following CME via the Hif1a/Ptgs2 pathway.